2020
DOI: 10.1186/s10194-020-01174-7
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic stimulation of the motor cortex alleviates neuropathic pain in rats of infraorbital nerve injury with/without CGRP knock-down

Abstract: Background: Previous studies have reported that electrical stimulation of the motor cortex is effective in reducing trigeminal neuropathic pain; however, the effects of optical motor cortex stimulation remain unclear. Objective: The present study aimed to investigate whether optical stimulation of the primary motor cortex can modulate chronic neuropathic pain in rats with infraorbital nerve constriction injury. Methods: Animals were randomly divided into a trigeminal neuralgia group, a sham group, and a contro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…These sensory nerve fibers are mainly Aδ-and C-fibers, and their cell bodies are rooted in the trigeminal ganglion (TG). Nociceptive signals are conveyed through these trigeminal afferents and projected to the trigeminal spinal caudalis (Vc) nucleus of the brainstem, where they synapse with the second-order neurons and are projected to the somatosensory and limbic cortices via reciprocal aberrant sensory signals assembled in the sensory area of the thalamus (i.e., the VPM), thereby initiating pain sensation and behavioral changes [2,[17][18][19][20][21]. Similar findings were observed in our study, with TN animals exhibiting painful behavioral responses in all behavior tests.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These sensory nerve fibers are mainly Aδ-and C-fibers, and their cell bodies are rooted in the trigeminal ganglion (TG). Nociceptive signals are conveyed through these trigeminal afferents and projected to the trigeminal spinal caudalis (Vc) nucleus of the brainstem, where they synapse with the second-order neurons and are projected to the somatosensory and limbic cortices via reciprocal aberrant sensory signals assembled in the sensory area of the thalamus (i.e., the VPM), thereby initiating pain sensation and behavioral changes [2,[17][18][19][20][21]. Similar findings were observed in our study, with TN animals exhibiting painful behavioral responses in all behavior tests.…”
Section: Discussionmentioning
confidence: 99%
“…The spinal trigeminal nucleus conveys craniofacial somatosensory information to the thalamus from the brainstem. Earlier studies also showed that TN is associated with anatomical and biochemical changes in the VPM thalamus that cause thalamic tonic firing hyperresponsiveness and an increase in the burst firing rate [1,2,[53][54][55]. Since stimulation of the NAcc causes alteration in its robust interconnections with areas involved in pain circuitry, manipulation of these networks produces antinociception with downstream effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations